Pedoman Pembinaan Narapidana Pelanggar Tata Tertib Berdasarkan Permenkumham Nomor 8 Tahun 2024 di Lapas Kelas IIA Yogyakarta - Risyat, Ibnu Arif; Sutopo, Soleh Joko; Kusuma, Izeda Tendi; Mustikaningtyas, Mustikaningtyas; Widayaningsih, Titi Pratiwi; Marina, Eva; Subekti, Ayuk Rahadhian (Wajah Hukum, 2024)
Based on the Regulation of the Minister of Law and Human Rights  Number 8 of 2024, security in prisons and detention centers is divided into 3 (three), namely: prevention, action and recovery. Then, the same regulation states that recovery is divided into 3 parts, namely: reconciliation, rehabilitation, and reconstruction. In reality, there is no recovery program regulated by the Directorate General of Corrections so that it can be used as a guideline by all prisons and detention centers regarding the recovery program. So the author created a Guideline for the Guidance of Prisoners Who Violate Order which can then be used as literacy material for all prisons and detention centers in Indonesia. The research method used by the author in this scientific article is normative, which means that research refers to regulations that can be analyzed and then linked to the current situation and after that the author can provide recommendations to be applied in the future. The legal basis in this scientific article is in accordance with the title of the article, namely PERMENKUMHAM No. 8 of 2024 and is linked to Law No. 22 of 2022 Concerning Corrections. This guideline provides an overview of each stage of recovery. Starting from reconciliation which is carried out for 7 (seven) days with emphasis on maximum block placement, mediation, assessment and psychological facilities. Then, rehabilitation which is carried out for 3 (three) months with an emphasis on providing training programs, assessments, and psychological facilities. Finally, reconciliation which emphasizes environmental improvement, assessment, and evaluation.